Toad rage - Gleitzman, Morris (New York : Random House, 2004)
Determined to understand why humans hate cane toads and toimprove relations between the species, Limpy embarks on a dangerous trek from his swamp to the Summer Olympics in Sydney, Australia.
Booklist
School Library Journal
Wilson's Children
5.5
3-6.
3-6
Keywords: Adventure and adventurers -- Fiction; Giant toad -- Fiction; Human-animal relationships -- Fiction; Toads -- Fiction; Adventure fiction; Giant toads -- Fiction; Human-animal relationship -- Fiction; Olympic Games, 2000 (Sydney, N.S.W.) -- Fiction; Toads -- Fiction; Australia -- Fiction; Sydney (N.S.W.) -- Fiction; Australia -- Fiction; Sydney (N.S.W.) -- Fiction